Tonal and Rhythmic-Metric Process in Brahms's Early C-Minor Scherzos - McClelland, Ryan (Intersections, 2005)
The scherzos Brahms composed for his Piano Quintet in F Minor, Op. 34 (1862; rev. 1864) and for the Dietrich-Schumann-Brahms F-A-E violin sonata (1853) are dramatic, C-minor pieces that allude to works of Beethoven's middle period. Both scherzos open with tonal and rhythmic-metric dissonance and end with tonal and rhythmic-metric consonance, yet there are significant refinements in Brahms's handling of these global progressions in the piano quintet scherzo. The piano quintet scherzo engages a smaller network of interrelated dissonances, intensifies these dissonances throughout the movement, and resolves them convincingly near the end of the scherzo.